2018
DOI: 10.1038/s41467-018-06486-6
|View full text |Cite
|
Sign up to set email alerts
|

HSP90-incorporating chaperome networks as biosensor for disease-related pathways in patient-specific midbrain dopamine neurons

Abstract: Environmental and genetic risk factors contribute to Parkinson’s Disease (PD) pathogenesis and the associated midbrain dopamine (mDA) neuron loss. Here, we identify early PD pathogenic events by developing methodology that utilizes recent innovations in human pluripotent stem cells (hPSC) and chemical sensors of HSP90-incorporating chaperome networks. We show that events triggered by PD-related genetic or toxic stimuli alter the neuronal proteome, thereby altering the stress-specific chaperome networks, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(117 citation statements)
references
References 82 publications
(120 reference statements)
4
113
0
Order By: Relevance
“…Why was epichaperome formation necessary under each stress? We observed that under toxic stress these epichaperomes remodeled dopamine production pathways, whereas under genetic stress they enhanced the fitness of inflammatory pathways along with other mechanisms (61). Thus, as we discussed in cancer (22), epichaperomes act by maintaining the and c, native protein separation and analysis by isoelectric focusing followed by immunoblotting with native cognate antibodies are used for minute biopsy specimens.…”
Section: Proteome Imbalance Drives Epichaperome Formationmentioning
confidence: 88%
See 4 more Smart Citations
“…Why was epichaperome formation necessary under each stress? We observed that under toxic stress these epichaperomes remodeled dopamine production pathways, whereas under genetic stress they enhanced the fitness of inflammatory pathways along with other mechanisms (61). Thus, as we discussed in cancer (22), epichaperomes act by maintaining the and c, native protein separation and analysis by isoelectric focusing followed by immunoblotting with native cognate antibodies are used for minute biopsy specimens.…”
Section: Proteome Imbalance Drives Epichaperome Formationmentioning
confidence: 88%
“…Recent work has shown that a significant driver of epichaperome formation is proteome imbalances (46,61). We identified one factor, MYC hyperactivation, to be partly responsible for driving the "rewiring" of the chaperome into the epichaperome in cancer (22,46,104).…”
Section: Proteome Imbalance Drives Epichaperome Formationmentioning
confidence: 93%
See 3 more Smart Citations